2020
DOI: 10.1016/j.mayocp.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cavernous Malformation: What a Practicing Clinician Should Know

Abstract: Cavernous malformations (CMs) are angiographically occult, low-flow vascular malformations of the central nervous system. They are acquired lesions, with approximately 80% of patients having the sporadic form and 20% the familial form of the disease. The lesions may also develop years after radiotherapy. At the microscopic level, they consist of endothelium-lined cavities (or "caverns") containing blood of different ages. The endothelium proliferates abnormally, and tight junctions are absent or dysfunctional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 98 publications
(130 reference statements)
0
44
0
Order By: Relevance
“…The current study identified a novel frameshift mutation in CCM1 (c.1635delA) in a Chinese family with CCMs. In this three-generation family with 20 family members, about 30% of them (six members) have developed CCMs with multiple lesions that are the common features of FCCMs (Zafar et al, 2019;Flemming and Lanzino, 2020). The positive family history in which CCMs are present in the proband, her maternal grandmother, her mother, and her uncles indicated an autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The current study identified a novel frameshift mutation in CCM1 (c.1635delA) in a Chinese family with CCMs. In this three-generation family with 20 family members, about 30% of them (six members) have developed CCMs with multiple lesions that are the common features of FCCMs (Zafar et al, 2019;Flemming and Lanzino, 2020). The positive family history in which CCMs are present in the proband, her maternal grandmother, her mother, and her uncles indicated an autosomal dominant inheritance.…”
Section: Discussionmentioning
confidence: 89%
“…The majority of CCMs are sporadic, covering over 90% of all cases while familial CCMs (FCCMs) only account for 6-7%, which is considered as a rare disease (Moriarity et al, 1999a;Batra et al, 2009;Spiegler et al, 2018;Zafar et al, 2019). However, less than 20% of patients with sporadic CCMs have multiple lesions (Moriarity et al, 1999b;Dammann et al, 2017;Flemming and Lanzino, 2020), whereas over 50% of FCCMs cause multiple CCM lesions, which will increase the risk of developing epilepsy and intracranial hemorrhage (Russo et al, 2017;Zafar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first reports of disease-causing CCM1 variants in familial CCM cases (Laberge-le Couteulx et al, 1999;Sahoo et al, 1999), we have learned a lot about CCM pathogenesis and the endothelial dysfunction in cavernous lesions (Maddaluno et al, 2013;Cuttano et al, 2016;Zhou et al, 2016;Detter et al, 2018;Malinverno et al, 2019;Hong et al, 2020;Ren et al, 2021). A first expert consensus guideline and clinical recommendations for CCM management have been published in recent years (Akers et al, 2017;Flemming and Lanzino, 2020). However, there are still no effective drugs that would prevent cavernoma formation or CCM bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms may occur at any age, although the typical age of onset is between the second and fifth decade of life and without sex predominance, even though the available data are conflicting. Moreover, the majority of CCM lesions remain clinically and biologically quiescent during the most of the host's lifetime [4][5][6] . To date, diagnosis is made only by magnetic resonance imaging (MRI), and it is mainly possible only when lesions become symptomatic [3] .…”
Section: Introductionmentioning
confidence: 99%